South African Female Principals’ Career Paths: Understanding the Gender Gap in Secondary School Management - Moorosi, Pontso (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2016)
This article reports on data from a larger scale study exploring female principals’ experiences of their career route to the principalship of secondary schools in South Africa. To understand these experiences, the study used an analytical framework that identifies three phases principals go through on their career route, namely: anticipation, acquisition and performance. The framework suggests that women experience more obstacles than men on their career route and their experiences are influenced by personal, organizational and social factors. These factors manifest in social practices within and outside schools and affect women across the three phases of the career route. Central to these experiences, is the underlying male norm of who is more appropriate for secondary school principalship.